The Effect of Job Statisfaction And Moral Reasoning on The Commitment of Auditors at The South Sulawesi Provincial Inspectorate Office - Tenriwaru Tenriwaru; Magfiratul Rahmadhani; Sitti Hartati Hairuddin (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Parepare, 2022)
The public accounting profession is a very important profession. This study aims to determine the effect of Job Statisfaction and Moral Reasoning on Auditor Commitment at the Inspectorate Office of South Sulawesi Province. This study uses primary data by conducting direct research in the field by distributing questionnaires/statement sheets to 47 respondents. The data analysis method used to test the hypothesis was multiple linear regression. The independent variables used in this study were Job Statisfaction and Moral Reasoning while the dependent variable used in this study was Auditor Commitment. The results showed that Job Statisfactio and Moral Reasoning had a positive and significant effect on Auditor Commitment because the higher the Job Statisfaction and Moral Reasoning, the higher the Auditor's Commitment to work.